The Study On The Death Khairat Fund Scheme (dkfs) As A Halal Service Scheme In The Islamic Financial System At Malaysia: An Analysis From Islamic And Law Views - Setiyawan Gunardi; Azman Ab. Rahman; Ahmad Zaki Salleh; Syed Mohd Najib Syed Omar; Khairunneezam Mohd Noor; Zawin Hannan Sofea Shahbuddin (SEYBOLD PUBLICATIONS, 2024)
Non-Indexed Publication